Synthesis and Physico-Chemical Characterization of a New Non-Centrosymmetric Organic Cation Iodate - Dhiab, A.C.; Sta, W. Smirani; Rzaigui, M. (JOURNAL OF ADVANCES IN CHEMISTRY, 2011)
The synthesis, crystal structure and physico-chemical characterization are presented for the piperazinium bis iodate dihydrate. An X-ray investigation has shown that this compound crystallizes in a non-centrosymmetric monoclinic system, space group Pc with the lattice parameters: a = 8.969 (2) Å, b = 6.027 (3) Å, c = 11.958 (2) Å; V = 612.7 (3) Å3 and Z = 2. The structure was solved from 3546 independent reflexions with R1 = 0.053 and wR2 = 0.130. I…O halogen bonds [R22(4) graph-set motif] range between 2.770 (4) and 3.108 (1) Å and connect neighboring IO-3 anions with each other so as to create a bi-dimensional layer parallel to the (b,c) plane. These layers are interconnected via N−H…O and C−H…O, to the piperazinium dication to generate a three-dimensional network.